Body Transformations in Drawings the Artist Muhammed Mehraddin: حسن طالب جنزي (Al-Academy, 2020)
The body concept in the human sciences received significant attention through study and investigation, and has been dealt with by many studies, yet this research is an attempt to reveal the body transformations and its concept in the visualized picture (drawing field) in general and in the drawings of the artist Muhammed Mehraddin in specific. Therefore, the approach of the body, philosophically and technically, in this field has its nature and specificity in revealing the structures and relations in employing the body as a visual, spatially and temporally indicator through the drawing fields of the artist Muhammed Mehraddin, assuming that the body, for the artist's works, constitutes a cultural, artistic performance focus in his artistic career. The first chapter of the research dealt with the procedural framework represented by the research problem and the need for it, the research objective, importance and limits. The second chapter presented the theoretical framework consisting of three sections: the first entitled (the concept of the body cognitively). The second section (the concept of the body artistically), and the third section deals with the referential foundations in the works of the artist Muhammed Mehraddin. The third chapter consists of the research procedures. The fourth chapter consists of the results and conclusions to mention some of them: the body witnessed technical, stylistic and performance transformations in the works of the artist Muhammed Mehraddin